Critical ventilation velocity under the blockage of different metro train in a long metro tunnel. (5th February 2020) - Zhang, Shaogang; Shi, Long; Li, Xianbin; Huang, Yilong; He, Kun; Wang, Jinhui
Summary: To address the effect of metro train blockage on the critical ventilation velocity in a long tunnel, a series of scenarios were conducted numerically through this study, including different fire sizes (5‐10 MW), metro train lengths (80‐120 m), and blockage ratios ( φ, 0.50, and 0.57). It is known from the numerical results that the metro train length shows a limited effect on the critical ventilation velocity, which is because the longitudinal ventilation has become stable before reaching the fire source to prevent smoke back‐layering, and increasing the metro train length only increases the distance of stabilizing the longitudinal ventilation. The blockage ratio shows an obvious influence on the critical ventilation velocity, which is because the presence of the metro train can obviously reduce the flow cross‐sectional area of the tunnel. An empirical model is developed as well, while it is known that the critical ventilation velocity increases with the one‐third power of dimensionless heat release rate and (1‐ φ ). The research outcomes of this study provide a technical guide for the design of the metro tunnel and the relevant emergency management of fire rescue under fire conditions.